Gas Phase Synthesis of Multifunctional Fe‐Based Nanocubes. (25th January 2017) - Vernieres, Jerome; Steinhauer, Stephan; Zhao, Junlei; Chapelle, Audrey; Menini, Philippe; Dufour, Nicolas; Diaz, Rosa E.; Nordlund, Kai; Djurabekova, Flyura; Grammatikopoulos, Panagiotis; Sowwan, Mukhles
Abstract : Magnetron‐sputtering inert‐gas condensation is an emerging technique offering single‐step, chemical‐free synthesis of nanoparticles with well‐defined morphologies optimized for specific applications. In this study, the authors report a flexible approach to produce Fe nanocubes as building blocks for high‐performance NO2 gas sensor devices, and hybrid FeAu nanocubes with magneto‐plasmonic properties. Considering that nucleation happens within a short distance from the sputtering target, the authors utilize the high‐permeability and resultant screening effect induced by magnetic Fe targets of various thicknesses to manipulate the magnetic field configuration and plasma confinement. The authors thus readily switch from bimodal to single‐Gaussian size distributions of Fe nanocubes by modifying their primordial thermal environments, as explained by a combination of modeling methods. Simultaneously, the authors obtain a material yield increase of more than one order of magnitude compared to experiments using postgrowth mass filtration. The effectiveness of the method is demonstrated by the deposition of Fe nanocubes on microhotplate devices, leading to unprecedented NO2 detection performance for Fe‐based chemoresistive gas sensors. The exceedingly low detection limit down to 3 ppb is attributed to a morphological change in operando from Fe/Fe‐oxide core/shell to specific hollow‐nanocube structures, as revealed by in situ environmental transmission electron microscopy. Abstract : A flexible gas‐phase synthesis method is demonstrated for the fabrication of multifunctional hybrid Fe nanocubes by means of morphological control during formation. Utilizing this approach, magneto‐plasmonic properties of Fe nanocubes are tailored by Au‐doping, and Fe‐based gas sensors are realized with remarkable performance for NO2 detection down to concentrations as low as 3 ppb.